Mapping Digital Accessibility for Students with Disabilities: A Case Study of Aligarh’s Public Schools Under the NEP 2020 Framework - Zaidan Mansoor Alig; Farhana Syeda (PT. Berkah Smart Academica, 2026)
This study aims to map digital accessibility for students with disabilities in public secondary schools across Aligarh, Uttar Pradesh, under the framework of the National Education Policy (NEP) 2020. Diverging from prior studies that primarily focused on hardware counts, this research fills a critical gap by evaluating the functional usability of digital infrastructure in the local Indian context. Utilizing a mixed-methods approach with a descriptive case study design, the study audited the digital ecosystems of 40 schools using an instrument based on the POUR indicators (Perceivable, Operable, Understandable, Robust) of the WCAG 2.1 standards. Mapping results indicate a severe